2019
DOI: 10.1186/s12876-019-0957-5
|View full text |Cite
|
Sign up to set email alerts
|

In-depth characterization of the Wnt-signaling/β-catenin pathway in an in vitro model of Barrett’s sequence

Abstract: Background An altered Wnt-signaling activation has been reported during Barrett’s esophagus progression, but with rarely detected mutations in APC and β-catenin (CTNNB1) genes. Methods In this study, a robust in-depth expression pattern analysis of frizzled receptors, co-receptors, the Wnt-ligands Wnt3a and Wnt5a, the Wnt-signaling downstream targets Axin2, and CyclinD1, as well as the activation of the intracellular signaling kinases Akt and GSK3β was performed in an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Human oral squamous cell carcinoma [38] Upregulated Hepatocellular carcinoma [39] Upregulated Esophageal adenocarcinoma [66] Upregulated Colorectal adenomas [66] Downregulated FZD3…”
Section: Frizzledmentioning
confidence: 99%
See 1 more Smart Citation
“…Human oral squamous cell carcinoma [38] Upregulated Hepatocellular carcinoma [39] Upregulated Esophageal adenocarcinoma [66] Upregulated Colorectal adenomas [66] Downregulated FZD3…”
Section: Frizzledmentioning
confidence: 99%
“…A comparison between FZD2 knockdown and overexpression found that 889 genes varied in expression, many of which were identified to induce EMT, extracellular-matrix organization, cell adhesion, angiogenesis, and morphogenesis [ 41 ]. FZD2 is highly expressed in premalignant lesions preceding esophageal adenocarcinoma but is decreased in colorectal adenomas compared to normal tissue, suggesting FZD2 could be targeted differently to intercept early lesions depending on the tissue type [ 43 ]. The minimal expression of FZD2 in normal adult tissues, along with substantial evidence of EMT promotion, highlights the chemopreventive potential of targeting FZD2.…”
Section: Frizzleds In Cancer Emtmentioning
confidence: 99%
“…1a ). Interestingly, many of these factors contribute to the maintenance of epithelial homeostasis and regeneration in digestive tissues including colon and esophagus 8 , 28 , 29 . In line with this, an Ingenuity Pathway Analysis linked the LIGHT down-regulated transcriptome to processes such as cellular and tissue growth or development, epithelial to mesenchymal transition and cell-to-cell communication (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Barrett's esophagus and gastric ciliated metaplasia are considered precancerous conditions indicating increased risk to develop cancer, and MCCs were also frequently found in association with gastric adenocarcinoma (Bishop, Perrino, Ruzinova, & Brunt, 2015; Loy, 1994; Rubio, Kato, Kitagawa, Sugano, & Grimelius, 1988; Torikata & Mukai, 1990; Torikata, Mukai, & Kawakita, 1990). Dysregulation of Wnt signaling and alterations in ΔN‐tp63 were connected to Barrett's esophagus formation in the mouse and in humans (Clément, Braunschweig, Pasquier, Bosman, & Benhattar, 2006; Götzel et al, 2019; Lefort & Dotto, 2011; Wang et al, 2011). Additionally, gastric ciliated metaplasia in the mouse can be induced by loss of gastric H + /K + ATPase.…”
Section: Xenopus As Model For Mucociliary Diseasementioning
confidence: 99%